2018
DOI: 10.1038/s41586-018-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

Control of cardiac jelly dynamics by NOTCH1 and NRG1 defines the building plan for trabeculation

Abstract: In vertebrate hearts, the ventricular trabecular myocardium develops as a sponge-like network of cardiomyocytes that is critical for contraction and conduction, ventricular septation, papillary muscle formation and wall thickening through the process of compaction . Defective trabeculation leads to embryonic lethality or non-compaction cardiomyopathy (NCC) . There are divergent views on when and how trabeculation is initiated in different species. In zebrafish, trabecular cardiomyocytes extrude from compact my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
188
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(226 citation statements)
references
References 43 publications
13
188
0
1
Order By: Relevance
“…The endocardium becomes sculptured and forms domes filled with cardiac jelly. At the side where the endocardium contacts the myocardium, Nrg1 expressed by endocardial cells can interact with ErbB2/ErbB4 expressed by the cardiomyocytes (Del Monte‐Nieto et al, ). Notch1 regulates the proliferation of the cardiomyocytes that are added to the base of the forming trabeculations in the domes (Del Monte‐Nieto et al, ; Grego‐Bessa and others, ).…”
Section: From Linear To Four Chambered Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…The endocardium becomes sculptured and forms domes filled with cardiac jelly. At the side where the endocardium contacts the myocardium, Nrg1 expressed by endocardial cells can interact with ErbB2/ErbB4 expressed by the cardiomyocytes (Del Monte‐Nieto et al, ). Notch1 regulates the proliferation of the cardiomyocytes that are added to the base of the forming trabeculations in the domes (Del Monte‐Nieto et al, ; Grego‐Bessa and others, ).…”
Section: From Linear To Four Chambered Heartmentioning
confidence: 99%
“…At the side where the endocardium contacts the myocardium, Nrg1 expressed by endocardial cells can interact with ErbB2/ErbB4 expressed by the cardiomyocytes (Del Monte‐Nieto et al, ). Notch1 regulates the proliferation of the cardiomyocytes that are added to the base of the forming trabeculations in the domes (Del Monte‐Nieto et al, ; Grego‐Bessa and others, ). Bmp10 expression in the trabecular cardiomyocytes is an important regulator of trabecular growth, shown by the facts that (a) deletion of Bmp10 results in hypotrabeculation (Chen et al, ) and (b) overexpression of Bmp10 in hypertrabeculation (Pashmforoush et al, ).…”
Section: From Linear To Four Chambered Heartmentioning
confidence: 99%
“…These results demonstrate that myocardial inactivation of Rbpj in cTnT-Cre;Rbpj flox mice does not affect heart development and structure, nor does impair adult heart function, as it occurs with NOTCH signaling inactivation in the endocardium (4, 17, 18, 26, 30, 57). In contrast, Rbpj deletion driven by the Nkx2.5-Cre driver leads to VSD, DORV and BAV, phenotypes due to Nkx2.5 -mediated CRE activity in valve endocardial cells in which RBPJ mediates NOTCH signaling, with VSD being the likely cause of perinatal lethality of these mutants.…”
Section: Resultsmentioning
confidence: 69%
“…DLL4-NOTCH1 signaling is reflected by the endocardial expression of the CBF:H2B-Venus transgenic NOTCH reporter in mice (17). Conditional inactivation of Dll4, Notch1 or Rbpj in the endocardium, results in very similar phenotypes (more severe in Rbpj mutants) consisting of ventricular hypoplasia and impaired trabeculation (4, 17, 26), while myocardial deletion of Jag1 does not affect trabeculation (17). Later, NOTCH1 signaling in the endocardium is activated in a temporal sequence from the myocardium by the JAGGED1/2 ligands in a MIB1-dependent manner, to sustain ventricular compaction and maturation (17, 27).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have reported that CMs in zebrafish and mouse are polarized in the apicobasal axis and that at least in zebrafish CMs undergo apical constriction and depolarization as they delaminate and seed the trabecular layer (Jiménez-Amilburu et al, 2016;Li et al, 2016;del Monte-Nieto et al, 2018). However, how this polarity is regulated in CMs remains unknown.…”
Section: Mutations Inmentioning
confidence: 99%